Appropriate extended functions for X-FEM simulation of elastic-plastic crack growth with frictional contact - Elguedj, Thomas; Gravouil, Anthony; Combescure, Alain (European Journal of Computational Mechanics, 2006)
The eXtended Finite Element Method (X-FEM) was used with success in the past few years for Linear Elastic Fracture Mechanics. In this paper one proposes to extend this method to fatigue crack growth analysis in the case of conned plasticity with treatment of frictional contact on the crack faces. A new plastic enrichement basis is therefore extracted from HRR elds and introduced in X-FEM coupled with an augmented Lagrangian formulation and a radial return method for plastic ow. Comparisons are made for mode I and mixed mode loading with a nite element code and show good agreements.